Implementasi Kompetensi Abad 21 dalam Pembelajaran PAI: Integrasi 4C, Literasi, PPK, dan HOTS - Agus Joko Purwanto (MGMP PAI SMP BINTAN, 2026)
This study aims to analyze the implementation of 21st-century competencies in Islamic Religious Education (PAI) learning through the integration of 4C skills (critical thinking, creativity, collaboration, communication), literacy, Character Education Strengthening (PPK), and HOTS at SDN 2 Jatidatar. The study employed a qualitative approach with a case study design. Data were collected through classroom observations, interviews with teachers and students, and document analysis. The results show that 21st-century competencies are implemented through group discussions, problem-based learning, simple projects, and reflection on Islamic values. Literacy is developed through reading texts and using digital media, PPK through habituation of religious attitudes and teamwork, and HOTS through case analysis and problem-solving. This implementation encourages students to be active, critical, and collaborative.